The Overlap of Visions between the Scenographer and the Director in the Theatrical Show (Al-Academy, 2018)
After the spread of the function of the scenographer in the modern theater, his vision has become present in most of the theatrical works and because the director is the master of the work and the owner of the vision that appears in front of the audience, the overlap between the visions of each of them was required. This research is an attempt to detect the overlap and disengagement in the work of each of them.The research is divided into a methodological framework that included the research problem, importance, limits, and purpose, and then the definition of terms. In the theoretical framework, the research dealt with two theoretical sections that pave the way for raising ideas related to this subject: the first section (scenography and theatrical directing). The second section is (the overlap of the two visions of the designer and the director). The sample of the research was intentionally chosen which is the play (the Birth of Oblivion) and after the analysis of the show, according to the descriptive approach, a set of results emerged and the most important of which are: 1- Play scenes or lighting or accessories cannot be included according the views of the designer of the scenography on account of the external vision so that the elements of the scenography do not dominate the external vision. 2. The scenography design vision and the directing vision must match because both of them create a single audio-visual image. The research ends with a list of sources and a summary in English